Swelling characteristics and permeability evolution of anthracite coal containing expansive clay under water-saturated conditions. (1st November 2020) - Yang, Shuo; Wen, Guangcai; Yan, Fazhi; Li, Honglian; Liu, Yanbao; Wu, Wenbin
Highlights: The swelling characteristics of anthracite containing expansive clay under water-saturated conditions are determined. The swelling is mainly attributed to hydration swelling of the expansive clay in the coal. The hydration swelling of the expansive clay has a significant effect on the pore volume and permeability of coal. Abstract: Hydraulic technology is commonly used in enhanced coalbed methane recovery. This technology also causes the coal to remain in a high water content state for a long time, and the expansive clay inside the coal will swell in this high water content state. However, the swelling characteristics of the expansive clay and its effect on the permeability of the coal under water-saturated conditions are not clear. In this study, comparative experiments were conducted on dry coal, coal treated with 0.5% KCl solution, and water-saturated coal to analyze the swelling characteristics and permeability evolution of anthracite containing expansive clay. The scanning electron microscopy results revealed that the surface of the dry coal was flat and smooth, whereas that of the water-treated coal contained many dark areas with expansions of varying sizes. The swelling rate tests show that the volume of the water-treated coal increased by 12.5% compared to the kerosene-treated coal, which is mainly caused by the hydration swelling of the expansive clay. The low-temperature nitrogen adsorption tests show that hydration swelling can significantly reduce the cumulative pore volume of water-saturated coal, mainly the macropores and mesopores. The seepage tests show that the permeability of the water-saturated coal is lower than that of dry coal under varying effective stresses and gas pressures. The permeability damage rate of the water-saturated coal is significantly higher than that of the KCl solution-saturated coal, which also indicates that the expansive clay has a significant effect on the permeability of coal seams.